Antihypertensive effects of whey protein hydrolysate involve reshaping the gut microbiome in spontaneously hypertension rats - Peipei Dou; Xiaoyi Li; Xiaoxiao Zou; Kai Wang; Lei Yao; Zhuo Sun; Hui Hong; Yongkang Luo; Yuqing Tan (Food Science and Human Wellness)
Novel angiotensin-converting enzyme (ACE) inhibitory peptides were identified from whey protein hydrolysates (WPH) in vitro in our previous study and the antihypertensive abilities of WPH in vivo were further investigated in the current study. Results indicated that WPH significantly inhibited the development of high blood pressure and tissue injuries caused by hypertension. WPH inhibited ACE activity (20.81%, P < 0.01), and reduced renin concentration (P < 0.05), thereby reducing systolic blood pressure (SBP) (12.63%, P < 0.05) in spontaneously hypertensive rats. The increased Akkermansia, Bacteroides, and Lactobacillus abundance promoted high short chain fatty acid content in feces after WPH intervention. These changes jointly contributed to low blood pressure. The heart weight and cardiomyocyte injuries (hypertrophy and degeneration) were alleviated by WPH. The proteomic results revealed that 19 protein expressions in the heart mainly associated with the wingless/integrated (Wnt) signaling pathway and Apelin signaling pathway were altered after WPH supplementation. Notably, WPH alleviated serum oxidative stress, indicated by the decreased malondialdehyde content (P < 0.01), enhanced total antioxidant capacity (P < 0.01) and superoxide dismutase activity (P < 0.01). The current study suggests that WPH exhibit promising antihypertensive abilities in vivo and could be a potential alternative for antihypertensive dietary supplements.